PENGGUNAAN REFERENSI PERSONA DALAM CERPEN HUJAN DAN RASA YANG HILANG: PENDEKATAN ANALISIS WACANA - Rustan, Megawati; Eka Nuriati , Agustin; Sumarlam , Sumarlam (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to analyze the use of persona references in the short story entitled Hujan dan Rasa yang Hilang by Tamara Rangkuti which was published in IDN Times on September 3, 2024. This study uses a qualitative descriptive method with a critical discourse analysis approach. The data in this study are in the form of utterances and dialogues in the short story Hujan dan Rasa yang Hilang which contain the use of persona references. The data collection method uses the listening method and note-taking technique. Then the data is analyzed using the distribution method with the basic technique used being the direct element division technique. The results of the study show that the short story contains personal pronominal reference forms including 1 second person singular free plural, 1 second person singular bound attached right, 9 third person singular bound attached right, and 8 third person singular free form. Then, the personal references were analyzed based on their place obtained from exophoric references found as many as 6, 11 anaphoric endophoric, and 2 cataphoric endophoric. This analysis shows that the use of references helps build cohesion and coherence in the short story text and strengthens the emotional relationship between the main character and the love story he faces.